2018
DOI: 10.1111/jvs.12647
|View full text |Cite
|
Sign up to set email alerts
|

Water source partitioning among plant functional types in a semi‐arid dune ecosystem

Abstract: Question(s):The aim of this work was to characterize the main water sources used by the woody plant community of a semi-arid coastal dune ecosystem. We ask: Do the seasonal water sources used by plants differ between functional types? Does the seasonal drought promote shifts towards deeper soil layers in all plants? Does greater use of deep soil water enables the maintenance of a more favorable plant water status? Do water-sources-use strategies mirror overall drought strategies?Location: Semi-arid coastal dun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 71 publications
3
20
0
Order By: Relevance
“…Fifteen woody plant species, with distinct functional characteristics (Díaz Barradas, Zunzunegui, Tirado, Ain‐Lhout, & García Novo, ), were considered, and a total of 191 plants were sampled (Table ). In a previous study (Antunes, Díaz‐Barradas, Zunzunegui, Vieira, & Máguas, ), these species clustered in five water‐use functional groups, with distinct summer water‐use patterns, exploring soil water from shallower to deeper soil layers. The species in this study and their respective functional type classification are described in Table .…”
Section: Methodsmentioning
confidence: 72%
See 2 more Smart Citations
“…Fifteen woody plant species, with distinct functional characteristics (Díaz Barradas, Zunzunegui, Tirado, Ain‐Lhout, & García Novo, ), were considered, and a total of 191 plants were sampled (Table ). In a previous study (Antunes, Díaz‐Barradas, Zunzunegui, Vieira, & Máguas, ), these species clustered in five water‐use functional groups, with distinct summer water‐use patterns, exploring soil water from shallower to deeper soil layers. The species in this study and their respective functional type classification are described in Table .…”
Section: Methodsmentioning
confidence: 72%
“…Lignified woody stems of each individual selected for physiological measurements were also collected at the same dates of soil sampling (2–10 September 2013). Soil and twig sampling, storage and water extraction by vacuum distillation followed the methodology detailed in Antunes, Díaz‐Barradas, Zunzunegui, Vieira, and Máguas (), Ehleringer and Dawson (), West, Hultine, Jackson, and Ehleringer (). Oxygen stable isotope ratio analysis of all water samples was performed by headspace equilibration, on an Isoprime (Micromass, UK) IRMS, coupled in continuous flow mode to a Multiflow (Micromass, UK) auto‐sampler and sample equilibration system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive plants often have major impacts on water resources throughout an ecosystem and SIA can be used to investigate these (Antunes, Diaz‐Barradas, Zunzunegui, Vieira, & Maguas, ). Researchers measured the 18 O in xylem water and used a mixing model to partition the contribution of precipitation versus ground water in invasive acacia in Europe and showed that the species exhibits large seasonally plastic responses (Maguas et al, ).…”
Section: Plants and Soilsmentioning
confidence: 99%
“…Rain amount not only affects the depth and time of water infiltration into soil (Yang et al, 2014) but also affects the contribution of rainwater to plant growth (Duan et al, 2008). The interspecific difference of rain amount that plants use is related to their life forms (Dodd et al, 1998;Antunes et al, 2018). Annual plants initially use small rain (2−5 mm).…”
Section: Introductionmentioning
confidence: 99%